2016
DOI: 10.7439/ijasr.v2i1.2965
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Evolvulus alsinoides derived gold nanoparticles for medical applications

Abstract: Plant mediated synthesis of metallic nanoparticles is an increasing commercial demand due to the wide applicability in various areas such as electronics, catalysis, chemistry, energy, cosmetics and medicine. This is greatly due to their special features, which include unusual optical and electronic properties, high stability and biological compatibility, controllable morphology and size dispersion, and easy surface functionalization. In the present investigation, synthesis of gold nanoparticle is done by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…18 Using E. alsinoides leaf extract, Anbarasu et al observed the generation of spherical GNP with a diameter of 80 nm using SEM. 43 DSL study revealed that size distribution of the synthesized GNPs were in the range of 50-100nm with the highest fraction of 80.29nm as shown in Figure 13b, which matched the results of the SEM analysis. Markus et al studied the synthesis of GNP utilising the Root of Chinese Herb A. pubescens Maxim.…”
Section: Dls Analysis Of Gnp Synthesized Using Different Plant Extractssupporting
confidence: 79%
See 1 more Smart Citation
“…18 Using E. alsinoides leaf extract, Anbarasu et al observed the generation of spherical GNP with a diameter of 80 nm using SEM. 43 DSL study revealed that size distribution of the synthesized GNPs were in the range of 50-100nm with the highest fraction of 80.29nm as shown in Figure 13b, which matched the results of the SEM analysis. Markus et al studied the synthesis of GNP utilising the Root of Chinese Herb A. pubescens Maxim.…”
Section: Dls Analysis Of Gnp Synthesized Using Different Plant Extractssupporting
confidence: 79%
“…Anbarasu et al produced spherical GNPs using E. alsinoides leaf at room temperature under dark condition. 43 With a zeta potential value of -28.7mV, these GNPs with an 80nm diameter showed good biocompatibility and stability for over 4 weeks as shown in Figure 11a. Gopinath et al manufactured GNPs utilizing T. arjuna fruit extract.…”
Section: Zeta Potential Characterization Of Gnp Synthesized Using Dif...mentioning
confidence: 98%
“…Of AgNPs showing effect against the film Cytotoxicity assay with HepG2 cells Membrane damaging activity at fungicidal conc. Is not interfering with mammalian membrane Potent inhibitors and have good therapeutic potential [ 136 ] --------- ------------ Disc diffusion method Maximum activity against T. rubrum followed by C. albicans, C. tropicalis, and M. furfur ----- -------- [ 139 ] Gold Nanoparticles Candida Albicans Athlete's foot, rashes, Swelling and skin candidiasis ------------- ---------- Disc diffusion method against NCIM and MTCC microbes ---- ------ Potent inhibitors [ 141 ] Chitosan Nanoparticles Candida Albicans Skin candidiasis -------------- ------------ Microdilution suspectibility testing against C. albican ATCC 14053 Improve the liposome residence time and therapeutic effect ---------- --- High drug loading and potent inhibitors [ 142 ] Chitosan-silver nanoparticles composite Candida albicans, Candida spp. Skin candidiasis ------- ----- Liquid growth inhibition assay Fungal growth inhibition was significantly high ------ ----- Potential alternative for antifungal chemotherapy.…”
Section: Recent Topical Anti-fungal Drug Deliverymentioning
confidence: 99%
“…24 Gold nanoparticles produced using E. alsinoides also showed antimicrobial activity against S. typhimurium, Micrococcus luteus, and the fungus Trichophyton rubrum in the disk diffusion assay. 25…”
Section: Evolvulus Alsinoidesmentioning
confidence: 99%